Inclusive tourism: a qualitative analysis of obese people's travel experiences/ Christy Bidder, Boyd Sun Fatt and Spencer Hedley Mogindol - Bidder, Christy; Sun Fatt, Boyd; Hedley Mogindol, Spencer (Universiti Teknologi MARA, Perak, 2023)
Tourism development is expected to be inclusive. Besides being a massive economic driver, tourism is also a significant social and economic integration vehicle. But how inclusive is tourism? A review of inclusive tourism literature reveals that even within this tourism niche, there is an imbalance of representation where differently-abled people, local communities, and poor people are emphasized more than obese individuals. Based on this background, this study examines one of the less-represented marginalized travel groups, namely obese travellers, focusing on the issues encountered by this underserved travel market. A case study design is used because there is scant information on obese travel, particularly within the Malaysian context. Data are collected from secondary records and personal interviews. Purposive sampling is used to select the study's initial subjects, and snowball sampling is used to recruit subsequent subjects. A step-by-step directed approach to content analysis is employed to analyze the interview transcripts. The key findings reveal that while flying is the most formidable obstacle in the physical process of travelling, emotional issues are the most challenging for obese travellers. The emotional difficulties make it difficult for obese travellers to fulfil their needs for love and belonging, esteem, and self-actualization while travelling. Thus, while physical support is crucial to creating a safe and comfortable travel experience for obese travellers, emotional support is the most significant support they need.